Steryl glucosides: a genetic approach to determine their role in cellulose synthesis and lipid metabolism in Arabidopsis - Stucky, Daniel Floyd (Kansas State University, 2013)
Steryl glucosides (SGs) are a common conjugate of sterols found in the plasma membranes of most plants and fungi, but their cellular functions remain largely unknown. Glycosylation of the C3 hydroxyl group of the sterol nucleus is catalyzed by UDP-glucose:steryl glucosyltransferase 80 (UGT80) enzymes. Two genes encoding UGT80A2 and UGT80B1 are responsible for most SG production in Arabidopsis thaliana, while UGT80C1 presents a putative third enzyme. In Arabidopsis, seed imbibition signals the epidermal seed coat cells to secrete an encapsulating mucilage that consists primarily of hydrated polysaccharides. Cellulose has been identified in the inner layer of the mucilage, providing a convenient model to study cellulose synthesis since seed mucilage is dispensable for viability and pectin and cellulose staining dyes are readily available. A reverse genetics and biochemical approach was used to characterize the role of UGT80 enzymes and their impact on cellulose synthesis in seed mucilage. ugt80B1 mucilage was found to have elongated cellulosic rays, but no defects in pectin synthesis. A double mutant of ugt80B1 and mum3-1, a mutant allele of CELLULOSE SYNTHASE 5 (CESA5), displays a novel phenotype with irregular cellulose patterning and extreme shedding of the pectinaceous layer surrounding the seed coat. The observed mucilage defects may be indicative of disrupted cellulose synthesis and a mechanistic relationship between SGs and the cellulose synthase machinery. UGT80A2 and B1 demonstrate glycosylation activity with a multitude of plant sterols. The two enzymes do display some substrate specificity, however, with UGT80A2 producing the large majority of sitosterol and stigmasterol glucoside compared to B1. UGT80C1 shows little or no sterol glucosyltransferase activity in vitro or in vivo and likely has evolved a different function from the two other genes. GFP:UGT80C1 expressed either from the constitutive 35S or from its native promoter was localized to lipid droplets and possibly chloroplasts as well, creating a new perspective on the role of the protein in plant lipid metabolism. This study extends the currently limited view of SGs as ubiquitous components of the plasma membrane to active regulators of cellulose synthesis in seeds. Evidence presented here changes the perceived role of the plant conserved protein, UGT80C1, from a putative steryl glucosyltransferase enzyme to having a function in intracellular lipid droplets.
Keywords: Steryl glucosides; UGT80; Cellulose; Lipids; Arabidopsis; Biochemistry (0487); Biology (0306)